The Role of Humor in Developing Students’ Creative Writing and Cultural Awareness: A Qualitative Case Study - Fithriyah Inda Nur Abida; Diana Budi Darma; Risman Iye (Journal of Innovative and Creativity (Joecy), 2026)
This study explores the role of humor in developing students’ creative writing skills and cultural awareness in higher education contexts. Employing a qualitative case study design, the research involved undergraduate students enrolled in a Creative Writing course at Universitas Negeri Surabaya. Data were collected through semi-structured interviews, classroom observations, and analysis of students’ literary works produced through humor-based learning activities. The findings reveal that humor serves as an effective pedagogical resource that stimulates imagination, facilitates idea generation, and creates an enjoyable learning environment that encourages active participation in writing activities. Students demonstrated improvements in thematic originality, creative expression, imagery, and the ability to reinterpret everyday experiences through literary language. Furthermore, humor contributed to the development of cultural awareness by enabling students to reflect on social realities, local traditions, and cultural values embedded in humorous narratives and experiences. Through the process of transforming humorous observations into literary texts, students developed a deeper appreciation of cultural diversity and a greater sensitivity toward social issues within their communities. Despite challenges related to diction, figurative language, and maintaining stylistic consistency, the findings suggest that humor-based learning provides an innovative and meaningful approach to creative writing instruction. The study highlights the potential of humor as both an affective and experiential learning resource for fostering creativity, cultural literacy, and reflective engagement in literary education.